2015
DOI: 10.1080/02786826.2015.1056337
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Trajectory and Capture of Fine Dust by Magnetic Mesh Filters Based on a Particle Velocity Model

Abstract: The particle velocity model developed in this study described the dynamic motion of fine dust particles along the magnetized mesh wires in a low Stokes regime. The numerically evaluated velocity contour of the particles modeled the critical path lines indicating the threshold positions for magnetic collection. The velocity contour was determined using the parameters such as particle size, magnetic intensity, flow velocity, and mesh configuration including wire thickness and packing density. Particle size was o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…In addition to making a long-surviving electret, magnetic force was used by incorporating magnetic particles in fibers [ 66 , 67 , 68 ]. In a study by Kim et al [ 69 ], poly(vinylpyrrolidone) (PVP) was electrospun, dispersing Fe 3 O 4 magnetic nanoparticles in the pre-spinning solution.…”
Section: Materials For Superior Filtrationmentioning
confidence: 99%
“…In addition to making a long-surviving electret, magnetic force was used by incorporating magnetic particles in fibers [ 66 , 67 , 68 ]. In a study by Kim et al [ 69 ], poly(vinylpyrrolidone) (PVP) was electrospun, dispersing Fe 3 O 4 magnetic nanoparticles in the pre-spinning solution.…”
Section: Materials For Superior Filtrationmentioning
confidence: 99%
“…The water vapor transmission rate (WVTR) of the composite fabric was measured following KS K 0594:2015 testing methods for the water vapor transmission rate of textile fabrics [50]. A combined temperature and humidity chamber (PL-3KPH, Espec Corp., Osaka, Japan) was used.…”
Section: Measurement Of Water Vapor Transmission Rate (Wvtr)mentioning
confidence: 99%
“…In the design of dust-removal equipments, an electrostatic cyclone type household vacuum cleaner named 'Tatsumaki cyclone' [11] and a small three-stage mobile gas-solid separator with greatly optimized structure and size [21] were manufactured. In the aspect of numerical simulation, Huang [22] obtained the critical path line which reflects the threshold position of magnetic collection by simulating the particle velocity contour, indicating that the application of magnetized net filter can promote the collection of ferromagnetic dust or aerosol to some extent without any additional power or pressure resistance. Zhang [23] applied Fluent to simulate the dust removal efficiency of the wire-pipe ESP in a magnetic field environment, and found that the magnetic field has a more obvious effect under the conditions of high gas velocity and low working voltage.…”
Section: Introduction mentioning
confidence: 99%